EFEKTIVITAS OBAT KUMUR PROPOLIS, KLORHEKSIDIN DAN POVIDON IODINE TERHADAP INDEKS PLAK (Studi Mahasiswa Fakultas Kedokteran Gigi Universitas Islam Sultan Agung Semarang berusia 18-23 tahun) - Mayya Nailullathifah; Diyah Fatmasari; Ade Ismail A.K; Arlina Nurhapsari (Jurnal Medali, 2013)
Nowdays various chemical and herbal mouthwash has been circulating. Propolis is one of the herbal mouthwash product derived from bee Apis sp. While chlorhexidine and povidon iodin are chemical mouthwash known to control the plaque growth. Research’s objective determine the effect of propolis mouthwash to plaque index decrease, compared to mouthwash ‘chlorhexidine and povidone iodine.The study was conducted on students 18-23 years old from the Dentistry Faculty, Islamic University Sultan Agung Semarang. Samples were divided into three groups, each group consits of 11 people for mouthwash chlorhexidine, povidon iodin, and propolis. Measurement of plaque index using PHP (Patient Hygiene Performance Index) Plaque Index by Podshadley and Haley.The majority of criteria dental plaque before rinsing were moderate in the group propolis, chlorhexidine and povidon iodin. The majority of criteria dental plaque after rinsing are moderate in the propolis, chlorhexidine and povidone (p < 0,05) iodine. P-value from one way anova test on the plaque index after rinsing shows that plaque index mean was significantly different. The post hoc test showed plaque index decrease by propolis is equivalents to chlorhexidine and higher than povidon iodin. The research design was pre and post test control group.It was concluded that propolis mouthwash influence to plaque index decrease. Keywords: propolis, chlorhexidine, povidon iodin, plaque index